Exploring the Determinants of Financial Distress in ASEAN-5 Firms During the COVID-19 Pandemic - Dwi Alfiyanah; Ika Atma Kurniawanti (Journal of Enterprise and Development (JED), 2025)
Purpose: This study examines the relationship between profits, cash flows, leverage, and their effects on financial distress in publicly traded companies across the ASEAN-5 countries during the COVID-19 pandemic, spanning from 2020 to 2023.Method: Financial distress was measured using the Altman Z-score, and the analysis utilized panel data regression. To enhance the reliability of the results, the Fixed Effect Model (FEM) with robust standard errors was applied. The sample consisted of 3,065 firms and 10,750 firm-year observations, selected through purposive sampling from the Osiris database.Result: The findings show that long-term leverage significantly increases the likelihood of financial distress. In contrast, profit, operating cash flow, and the current ratio had no significant effect. These results emphasize the critical role that long-term debt structure plays in shaping financial vulnerability during systemic crises, such as pandemics.Practical Implications for Economic Growth and Development: This study offers valuable insights for corporate managers, investors, and policymakers in developing strategies to strengthen capital structure management. Reducing reliance on long-term debt can enhance corporate financial resilience, which, in turn, supports macroeconomic stability and promotes sustainable development.Originality/Value: This study contributes to the literature by focusing on the pandemic period in the ASEAN-5 region, utilizing a comprehensive cross-country and multi-year sample, and highlighting the significance of long-term leverage as a key factor in financial distress.